A comparison of equisedative infusions of propofol and midazolam for conscious sedation during spinal anesthesia - A prospective randomized study - Abhiruchi Patki; V C Shelgaonkar (Wolters Kluwer Medknow Publications, 2011)
Background : Supplemental sedation with an intravenous agent is often required to allay fear and anxiety in patients subjected to spinal anesthesia .We studied and compared the properties of propofol and midazolam as equisedative continuous infusions. Patients & Methods: 100, ASA grade 1 and 2 patients, 18 to 60 years of age, undergoing spinal anesthesia, were randomly allocated to receive either propofol 1mg/ml or midazolam 0.1mg/ml in 50ml syringes through syringe pump. The infusion rates were titrated in order to maintain a desired sedation score of 4 on the Observer's assessment of alertness/ sedation scale. Anxiety score was assessed at regular intervals by a single observer in all cases, using a 100mm visual analog scale.Intraoperative and postoperative amnesia was assessed using visual task of recall of pictures and verbal task of recall of words. Results: Propofol infusion was found to be superior to that of midazolam as it showed a statistically significant faster onset in achieving the desired sedation score, significantly lower mean anxiety scores, a clear headed, rapid recovery and significantly lesser postoperative impairment of recall, but midazolam infusion was seen to be associated with deeper intraoperative amnesia over the former which was beneficial. Conclusion: Equisedatine infusion of propofol & midazolam as an adjunct & spinal anesthesia offer good anxiolysis and cardio respiratory stability. Propofol her faster onset & recovery while midazolam provides better intraoperative annesia.